Free math problem solver answers your algebra, geometry, trigonometry, calculus, and statistics homework questions with step-by-step explanations, ...

People also ask

How to square root 6x squared?

What is 6 into the square root of 2?

What does 2 √6 mean?

Detailed step by step solution for simplify sqrt(6x^2)

Set the radicand in √6−x2 6 - x 2 greater than or equal to 0 0 to find where the expression is defined. 6−x2≥0 6 - x 2 ≥ 0. Step 2. Solve for x x .

Jul 24, 2023 · The way to solve it would be to derive A = W*L, so x*sqrt(6-x), set equal to 0, solve for x and determine maxima.

Jan 8, 2017 · x=6. Explanation: √x2=6. √x2=x. x=6. Check. √62=6. 6=6.

Aug 20, 2017 · By Minkowski (triangle inequality) we obtain: √x2−2x+1+√x2−6x+13=√(x−1)2+02+√(3−x)2+22≥. ≥√(x−1+3−x)2+(0+2)2=2√2.

x=sqrt(6x-1) Two solutions were found : x = 0.1716 x = 5.8284 Radical Equation entered : x = √6x-1 Step by step solution : Step 1 :Isolate the square root on ...

Feb 12, 2017 · Carlos W. asked • 02/12/17. Solve this equation by factoring square root 6 x^2-x-square root 6=0. I am struggling with this question.

The expression you've provided seems to be: 6x^2 * sqrt(80x) + x * sqrt(45x^3). Let's simplify this step by step. Step 1: Simplify the square roots.